The impact of COVID-19 on devolution : recentralising the British state beyond Brexit? - Morphet, Janice (Bristol shorts insights., 2021)
This topical book explores how the public perception of the UK decentralized governments has changed during the pandemic and uses case studies to discuss the actions taken by central government to undermine the devolution settlement, making a vital contribution to the future options for the UK within the context of Brexit and what follows.